Relationship between dynamic fatigue crack propagation properties and viscoelasticity of natural rubber/silicone rubber composites. Issue 51 (20th September 2019) - Han, Qingyuan; Zhang, Liqun; Wu, Youping
Abstract : The successfully established relationship between dynamic fatigue crack propagation behaviour and viscoelasticity of NR/VMQ composites. Abstract : In this paper, dynamic fatigue crack propagation properties of natural rubber/silicone rubber (NR/VMQ) composites are studied under constant tearing energy ( G ) input. Through dynamic fatigue crack growth testing, it is found that with the increase of VMQ fraction, NR/VMQ exhibits a lower crack growth rate (d c /d N ). The viscoelastic parameters have been recorded in real-time during crack propagation, including the storage modulus E ′, loss factor tan δ, and loss compliance modulus J ′′, and their relationships with crack propagation behaviour have been established. The improved crack propagation resistance is attributed to the reduced J ′′, resulting from the synergistic effect of increased E ′ and decreased tan δ, and thus more energy dissipation occurred in the linear viscoelastic region in front of the crack tip, which consumed part of the energy for crack growth. Finally, good correlation between d c /d N and J ′′ could be successfully established.